Ferroelectric HfO2 Capacitors for Varactor Application in GHz. (8th September 2020) - Lin, Yu Wei; Mizutani, Kazuto; Hoshii, Takuya; Wakabayashi, Hitoshi; Tsutsui, Kazuo; Tsao, Yi-Fan; Huang, Ting-Jui; Hsu, Heng-Tung; Kakushima, Kuniyuki
Abstract : The capacitance extraction of ferroelectric HfO2 capacitors was characterized at a frequency of 1GHz. By applying a bias voltage in the non-switching region of the ferroelectric HfO2 films, a varactor operation was confirmed.